Vulvar Lipoma: A Case Report - Shah, Ravi Kumar; Jaiswal, Arushi; Mushtaq, Rehana; Ansari, Sana; Shrestha, Ruby; Shah, Pravin; Deep, Jagat Prasad (Med Phoenix, 2025)
Introduction: This case report presents a rare instance of vulvar lipoma, a benign, slow-growing neoplasm of adipose origin. A 24-year-old unmarried woman presented with a painless, progressively enlarging vulvar mass. Ultrasound revealed a hyperechoic lesion suggestive of lipoma, confirmed by histopathology following surgical excision. While vulvar lipomas are extremely rare, surgical removal remains the preferred management in symptomatic cases.